THE FEMINIST IDEOLOGY OF PRESIDENT ABDEL FATTAH EL-SISI IN THE TEXT OF THE SPEECH FOR THE CELEBRATION OF EGYPTIAN WOMEN'S DAY - Saila Fadhila Ulfa; Alifia Zahratul Adha (CMES (Center of Middle Eastern Studies), 2023)
Compared to the Mohammed Morsi era, Abdel Fattah el-Sisi's regime has policies supporting women's rights and empowerment. Ironically, the facts indicate that the incidence of sexual harassment in Egypt during el-Sisi's administration remains high. This research discusses this issue by analyzing el-Sisi's Egyptian Women's Day speech. The study aims to uncover el-Sisi's ideology regarding the role of Egyptian women using Teun A. van Dijk's critical discourse analysis. The research is grounded in the gap between the discourse on women discussed in the text and social facts. It employs a qualitative descriptive method with the listen, read, and note technique. The research findings indicate that el-Sisi's speech reflects a liberal feminist ideology. His ideology constructs women as active participants in nation-building and contributors to the economic, social, and political sectors.